2010
DOI: 10.1002/biof.89
|View full text |Cite
|
Sign up to set email alerts
|

The plausibility of maternal nutritional status being a contributing factor to the risk for fetal alcohol spectrum disorders: The potential influence of zinc status as an example

Abstract: There is increasing evidence that human pregnancy outcome can be significantly compromised by suboptimal maternal nutritional status. Poor diet results in a maternal-fetal environment in which the teratogenicity of other insults such as alcohol might be amplified. As an example, there is evidence that zinc (Zn) can interact with maternal alcohol exposure to influence the risk for fetal alcohol spectrum disorders (FASD). Studies with experimental animals have shown that the teratogenicity of alcohol is increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 123 publications
(105 reference statements)
1
77
0
2
Order By: Relevance
“…45 Some evidence suggests that nutritional deficiencies during pregnancy magnify the deleterious effects of alcohol on the brain. 46,47 These children have substantial problems with memory and a poor understanding of the consequences of behavior, and they tend to be easily influenced by peers and make poor decisions in life. 48,49 For these reasons, youth with fetal alcohol spectrum disorders (FASDs) may be more likely to commit offenses and be detained.…”
Section: Fetal Alcohol Spectrum Disordersmentioning
confidence: 99%
“…45 Some evidence suggests that nutritional deficiencies during pregnancy magnify the deleterious effects of alcohol on the brain. 46,47 These children have substantial problems with memory and a poor understanding of the consequences of behavior, and they tend to be easily influenced by peers and make poor decisions in life. 48,49 For these reasons, youth with fetal alcohol spectrum disorders (FASDs) may be more likely to commit offenses and be detained.…”
Section: Fetal Alcohol Spectrum Disordersmentioning
confidence: 99%
“…To our knowledge, only 2 published studies have documented the effects of choline supplementation in clinical populations with or at risk of FASDs. The first study was published as part of a larger clinical trial that explored micronutrient supplementation in alcohol-consuming pregnant women in the Ukraine (11,12) and showed that choline supplementation improved neurophysiologic encoding and memory in both alcohol-exposed and -unexposed infants (13). The second study was a randomized clinical trial of choline supplementation in preschool-aged children with FASDs and revealed that choline improved memory function in young children between the ages of 2.5 and 5 y (14).…”
Section: Introductionmentioning
confidence: 99%
“…Значний вплив алкоголю протягом першого триместру пов'язаний з розвит-ком у плода структурних аномалій, включаючи ано-малії головного мозку; вживання алкоголю в друго-му триместрі підвищує ризик спонтанного аборту; а в третьому триместрі переважно впливає на вагу, довжину і зростання мозку [15]. Доведено, що нер-вові поведінкові ефекти можуть виникати навіть за відсутності лицевих або структурних аномалій го-ловного мозку [7,12,13].…”
Section: Yeletskayaelena@gmailcomunclassified
“…Значний вплив алкоголю протягом першого триместру пов'язаний з розвит-ком у плода структурних аномалій, включаючи ано-малії головного мозку; вживання алкоголю в друго-му триместрі підвищує ризик спонтанного аборту; а в третьому триместрі переважно впливає на вагу, довжину і зростання мозку [15]. Доведено, що нер-вові поведінкові ефекти можуть виникати навіть за відсутності лицевих або структурних аномалій го-ловного мозку [7,12,13].На тепер у англомовних виданнях широко ви-користовують термін «розлади фетоалкогольного спектру» -термін, який застосовується для опису фізичних, психічних, поведінкових та когнітивних ефектів, які можуть виникнути у осіб з впливом пренатального алкоголю [5,6]. Розлади фетоалко-гольного спектру не є діагностичним терміном, але включає групу специфічних захворювань з легкими та тяжкими фенотипами [11]: алкогольний синдром плоду (ФАС), частковий фетоалкогольний синдром (ЧФАС), неврологічний розлади внаслідок прената-льного алкоголю, нейро-поведінкові розлади, по-в'язані з експозицією пренатального алкоголю, вроджені дефекти, пов'язані з алкоголем (ВДПА) [3,4,8].…”
unclassified